Fruitlet Thinning Improves Juice Quality in Seven High-tannin Cider Cultivars - David L. Zakalik; Michael G. Brown; Gregory M. Peck (HortScience, 2023)
Over 3 years (2016–18), tree productivity, biennial bearing, return bloom, and fruit quality were evaluated for seven high-tannin cider apple (Malus ×domestica Borkh.) cultivars. Five treatments were evaluated on each of the seven cultivars: hand-thinned of all fruit (a zero crop load treatment); hand-thinned to crop densities of three, six, or nine fruit/cm2 trunk cross-sectional area (TCSA); or left unthinned. In this paper, we report on the fruit maturity and juice quality properties that were analyzed for the three nonzero crop load treatments and the unthinned control. The effects of crop load on fruit maturity, as measured by starch pattern index and preharvest drop, were cultivar dependent. Crop density (fruit/cm2 TCSA) had a significant effect on all fruit maturity and juice quality variables, although effects were weakest in the “off” year (2017) for the whole planting when initial fruit set was low. As crop density increased, total poly phenols, titratable acidity, soluble solids, and primary amino nitrogen decreased in the juice of all seven cultivars. A partial budget analysis indicated that the reduced costs of nitrogen supplements due to increased primary amino nitrogen concentration alone would not justify cost of chemical or hand-thinning. By extrapolating the spring flowering density in the fourth year to potential fruit yields at harvest, we found that reducing crop load was projected to increase cumulative total polyphenol yields per tree over the long term. For the cultivars in this experiment, a target crop density of nine fruit/cm2 was found to adequately decrease biennial bearing while also not diminishing juice quality for hard cider production. High-tannin cider apple growers should consider juice quality, particularly tannin production, when making crop load management decisions.